2004
DOI: 10.1002/bmb.2004.494032020322
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting a biochemistry course for physical education majors: A case study

Abstract: The purpose of this study was to investigate and analyze the events responsible for curricular characteristics that lead to positive outcomes in university teaching using a biochemistry course taught to physical education students as a model. The research was carried out as a case study, supported by questionnaires, classroom observation, document analysis, and interviews. The overall analyses of obtained data were validated by means of triangulation protocols, which proved the following reasons for the course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The relative ineffectiveness of lectures in developing students' understanding and skills relative to active learning methods is well known (6)(7) and also documented for biochemistry classes (8)(9)(10). Lectures also limit opportunities for the types of student-student and student-instructor interactions known to promote student learning and motivation (11). The author's previous experiences with this teaching approach in introductory biochemistry for nonmajors showed that lectures have a low effectiveness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relative ineffectiveness of lectures in developing students' understanding and skills relative to active learning methods is well known (6)(7) and also documented for biochemistry classes (8)(9)(10). Lectures also limit opportunities for the types of student-student and student-instructor interactions known to promote student learning and motivation (11). The author's previous experiences with this teaching approach in introductory biochemistry for nonmajors showed that lectures have a low effectiveness.…”
mentioning
confidence: 99%
“…This outcome is not hard to understand. Biochemistry and organic chemistry are traditionally difficult courses for nonmajors (4,11). Understanding monosaccharide isomers poses specific challenges: (i) an understanding of the underlying organic and general chemistry principles; (ii) a need for skills to infer three-dimensional structures from two-dimensional diagrams; (iii) motivating oneself to master topics of a very abstract and symbolic nature (12).…”
mentioning
confidence: 99%